Institutional integrated teletandem: What have we been learning about writing and peer feedback? - Aranha, Solange [UNESP]; Cavalari, Suzi Marques Spatti [UNESP] (FapUNIFESP (SciELO), 2015)
We define institutionally integrated teletandem (iiTTD) as a series of teletandem sessions that are embedded in regular foreign language lessons, so that such lessons both feed and are fed by teletandem practice. In this paper, we analyze prospective Brazilian teachers correcting American students' writing productions in Portuguese during their participation in an iiTTD. We address issues about how pre-service FL teachers (participants in iiTTD) offer writing feedback to their peers. Data included all the texts written and revised during the length of their partnership. Results show that most participants tend to correct their iiTTD partners' written productions in a direct way, focusing mainly on language form and according to their beliefs and experience as learners.
Keywords: Corrective feedback; Foreign language learning; Teletandem; Writing process